LARP3 inhibits the apoptosis of hepatocellular carcinoma via the ROS/PI3K/c-Fos axis. - Lin Zhu; Qianqian Meng; Weiyi Qian; Weiting Shao; Yuyue Lu; Shuai Jin; Afei Zhang; Shuang G Yan; Jingtao Lu (PLoS ONE)
Primary hepatocellular carcinoma (PHC) is the sixth most common cancer and the third leading cause of cancer death worldwide. Hepatocellular carcinoma (HCC) accounts for 75%-85% of PHC. LARP3 is aberrantly expressed in multiple cancers. We found that it is significantly highly expressed in the liver cancer tissues of HCC patients, but the exact role and specific mechanism of this abnormal expression are not yet clear. In this study, through bioinformatics analysis, we concluded that LARP3 expression is associated with a poor prognosis for patients with HCC. Through cellular experiments such as gene editing and phenotypic functions, we found that LARP3 promotes the occurrence and development of HCC and inhibits apoptosis. Finally, through biological means such as RNA sequencing, flow cytometry, western blotting, and the construction of a subcutaneous tumorigenesis model in nude mice, we concluded that inhibition of HCC apoptosis by LARP3 is related to LARP3 negatively regulating ROS level and inhibiting the PI3K/c-Fos/apoptosis axis. This study will provide potential targets for the treatment of HCC.